A roadmap to establish a comprehensive platform for sustainable manufacturing of natural products in yeast - Gita Naseri (Nature Communications, 2023)
Yeasts, Saccharomyces cerevisiae and Pichia pastoris, are promising chassis for the production of nature products (NPs). Here, the author discusses establishing a comprehensive platform for sustainable production of NPs via system-associated optimization at genetics, temporal controllers, productivity screening, and scalability levels.